Quality of commercial chicken cuts fresh and with seasoning in the southwest of Goiás (Research, Society and Development, 2020)
Due to the good acceptability and being an easily accessible and economically product for consumption, the production of chicken meat has been increasing in the last two decades.That said,it was aimed with this research to evaluate the microbiological, physicochemical quality of fresh and seasoned chicken meat commercialized in the city of Santa Helena de Goiás.The samples were collected in four commercial establishments  and then there were carried out microbiological analyzes for total, thermotolerant coliforms and Salmonella spp, physical and chemical analyzes for pH, acidity and water retention.The results obtained in the microbiological analyzes for total and thermotolerant coliforms showed that the samples were above the limits established by Normative Instruction No. 62, of 09/18/2003, by the Brazilian Ministry of Agriculture, Livestock and Supply.For Salmonella spp. evaluation the microorganism was present in 25g in three from the four samples evaluated.The pH of the samples ranged from 6.17 to 6.53, consistent with values found in the literature.A there was a small variation in the analyzed samples acidity.Only one sample, among the four evaluated showed higher water retention.Thus, it was possible to conclude that the fresh and seasoned chicken cuts analyzed were not in hygienic-sanitary conditions suitable for consumption.